L’État et les firmes multinationales - Faucher, Philippe; Niosi, Jorge (Études internationales, 1985)
The article argues that the state plays, and has always played, a key role in the internationalization of firms and that theoretical explanations of MNE should take that role into account. The first part of the paper deals with the place of the state in the theories of multinational firms ; most theories can be classified into three currents : those arguing the decline of the Nation-State as a consequence of the growth of MNE, those seeing the territorial expansion of the state as a natural consequence of multinationalism and those arguing the direct but weak thrust of the State in favour of MNE. The second section of the paper analyses the main types of government intervention pushing national firms into foreign operations. The third section studies the most evident case of government intervention on multinationalisation : the case of multinational state enterprises. The article concludes that the state should be included - an increasingly so - as a major purveyor of advantages to national firms seeking to initiate or pursue foreign activities.